2022
DOI: 10.3390/agronomy12123069
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization of Rice Grain Screening System Based on DEM–CFD Coupled Rice Seed Testing Platform

Abstract: Targeting the problems of low precision and heavy workload in conventional screening of filled and unfilled grain in single-plant rice testing, a screening system for filled and unfilled grain was designed based on the coupling of the wind and gravity fields. In this study, the motion state of filled and unfilled grain in the flow field and the results of screening were analyzed and combined with aerodynamics. In order to reveal the influence law of the structural and working parameters of the screening system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Based on the actual distribution of fruit and debris in the fruit collection box after completion of harvesting by the peanut combine in hilly mountainous areas, the simulation experiments mainly analyzed the suspension state of different kernels of peanuts and clay-heavy clods with different masses and shapes as well as different water contents. The experiments were based on the discrete element simulation software EDEM 2021.2 with the multi-sphere filling method to create parametric models of differently shaped particle entities (shown in Figure 4) [16], analyze particle movement of the peanut pods and clayheavy clods, and analyze the fluid dynamic properties based on Ansys 2022 R1 [17]. The physical and relevant action parameters of the particle model, derived from measurements, and a review of the relevant literature, are shown in Table 2 [18,19].…”
Section: Materials Model and Parameter Settingmentioning
confidence: 99%
“…Based on the actual distribution of fruit and debris in the fruit collection box after completion of harvesting by the peanut combine in hilly mountainous areas, the simulation experiments mainly analyzed the suspension state of different kernels of peanuts and clay-heavy clods with different masses and shapes as well as different water contents. The experiments were based on the discrete element simulation software EDEM 2021.2 with the multi-sphere filling method to create parametric models of differently shaped particle entities (shown in Figure 4) [16], analyze particle movement of the peanut pods and clayheavy clods, and analyze the fluid dynamic properties based on Ansys 2022 R1 [17]. The physical and relevant action parameters of the particle model, derived from measurements, and a review of the relevant literature, are shown in Table 2 [18,19].…”
Section: Materials Model and Parameter Settingmentioning
confidence: 99%